مسائل الإيمان في سورة الكهف - الفوزان، بدرية بنت محمد بن عبدالله (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بدمنهور, 2018)
الدلالات العقدية على مسائل الإيمان في سورة الكهف" سأتناول مسائل العقدية والإيمان المستنبطة من السورة، تنقسم الدراسة إلى تمهيد وفصلين وكل فصل فيه عدد من المباحث: التمهيد يشمل: أولاً: تعريف بالسورة ثانياً: القصص في السورة الفصل الأول: مسائل الإيمان المتعلقة بأركانه المستنبطة من السورة وسيكون في أربعة مباحث الأول: إثبات وحدانية الله، وتنزيهه سبحانه، الثاني: الإيمان بالرسل وإنزال الكتاب الثالث: توحيد الأسماء والصفات، الرابع: الإيمان باليوم الآخر والبعث. الفصل الثاني: مسائل الإيمان المتعلقة بالحياة وعالجتها السورة وفق منظور إيماني ويشمل عدد من المباحث تشمل عدد من قضايا الإيمان وشؤون الحياة وارتباطها بالإيمان. الخاتمة وفيها عدد من النتائج والتوصيات نهاية البحث.
Stochastic Significance on the Issues of Faith in Surat Al Kahf me will be addressing the issues of faith and doctrine in surah Al Kahf, which plays a role in correcting the conceptual approach and protecting mind and sense. Study breakdown: the study consists of an introduction and two chapters. Each chapter TEMPhas a number of researches. Introduction consists of acquainting of Surah Al-Kahf and the story. First chapter: doctrine issues surrounding pillars of faith in Surah Al-Kahf, It will be in four chapters. First, proof of the oneness of God. Second, believing in his messengers and his books. Third, believing in monotheism of Allah’s names and qualities. Forth, believing in the last day and the afterlife. Second chapter: Correcting the conceptual approach and consideration of life according to the perspective of faith and it consists of 14 reaserch. It covers a number of creed and life affairs issues and how it is linked to faith Finally, the conclusion and it TEMPhas several findings and recommendations.
Keywords: العقيدة الإسلامية -- مسائل العقيدة -- عقيدة الإيمان -- سورة الكهف